Development of Addie Model for Chapter Thaharah Learning Based on Game Applications in Junior High School - Mardianto Mardianto; Hasan Matsum; Dewi Sarmita (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This study aims to determine the effectiveness and attractiveness of using game application media to increase students' learning motivation. This research was conducted in Medan, North Sumatra because the teaching and learning activities (KBM) carried out at the school, especially in fiqh subjects, had used games and applications, it was just that they were still limited to using Microsoft PowerPoint media so that it still seemed less effective. This type of research uses research and development methods or it can also be called research and development. While the sample uses the Dick and Lou Carey development design method. While the samples were taken by class VII students of SMP IT Nurul Azmi Medan, using a one-group pretest and post-test design pattern. The data used is the daily test values ​​before and after being treated, then analyzed using the t-test. The results showed that the game application-based learning media used had a high level of effectiveness and attractiveness. The existence of fairly high interest and motivation to learn shows that there is a high interest of students in teaching and learning activities, especially during fiqh subjects. This finding is supported by field facts where the average daily test scores of students increased by 18.49% from 69.96% to 82.90%.